(untitled) (EAAE Annual Conference Proceedings, 2023)
This text describes an activity carried out in the teaching of the course Representation Methodologies for the Project (Master’s Degree Course in Architecture, University of Genoa, Italy). This course focuses on expanding the concept of accessibility for the configuration and communication of architecture through theory and practice.